Towards a consulting model for a good urban generation of social housing districts in terms of equipment - Lamyae Alaoui; sakina elhadi; Abdellah Lakhouili; Abdelaziz Merzak (Institute of Advanced Engineering and Science, 2024)
Social housing in Morocco is housing built with state assistance. It is subject to precise rules of construction, management and allocation and governed by specifications defining requirements in a manual manner. This work which is done manually can produce errors either at the level of calculations or at the level of equipment proposal. The objective of this article is to computerize this area as there is a lack of tools and platforms. To solve this problem, we have created an advisory platform for good urban planning for residents which will help engineers. Based on mathematical formulas. This tool will allow architects and urban planners to design autonomous populations in terms of equipment.